2012
DOI: 10.1155/2012/984561
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Use of Cigarettes and Smokeless Tobacco among US Males and Females

Abstract: Background. The current study describes concurrent use of cigarettes and smokeless tobacco (CiST) among males and females and evaluates factors associated with CiST use. Methods. Cross-sectional data were drawn from the 2010 Behavioral Risk Factor Surveillance System (BRFSS). Weighted stratified analyses were performed to find associations between CiST use and sociodemographic factors by gender. CiST users were compared to three different tobacco use groups: nonusers, exclusive smokers, and exclusive ST users.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 18 publications
7
29
1
Order By: Relevance
“…To compare our results with the literature of poly-use among current tobacco users, 13,16,[29][30][31][32][34][35][36][37][38][39] it is worth pointing out that previous poly-use prevalence estimates varied widely depending on types of tobacco products examined, frequency of tobacco use (daily vs. nondaily), and gender. In the literature, dual use of cigarettes with SLT (chewing tobacco and snuff) 16,30,31,35,36 and dual use of cigarettes with snuff 13,37 were the most commonly examined poly-use combinations.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…To compare our results with the literature of poly-use among current tobacco users, 13,16,[29][30][31][32][34][35][36][37][38][39] it is worth pointing out that previous poly-use prevalence estimates varied widely depending on types of tobacco products examined, frequency of tobacco use (daily vs. nondaily), and gender. In the literature, dual use of cigarettes with SLT (chewing tobacco and snuff) 16,30,31,35,36 and dual use of cigarettes with snuff 13,37 were the most commonly examined poly-use combinations.…”
Section: Discussionmentioning
confidence: 80%
“…At the population level, some studies estimated the prevalence of current polytobacco use among special populations such as the Lumbee American Indians in North Carolina (4.8%), 22 Air Force recruits (1.3%−3.3%), 5,23 active duty military personnel (11.5%), 24 college students (7.4%), 25 young adults aged 18−34 (7.0%), 26 and cancer prevention trial participants (3.7%), 27 while others estimated the prevalence of current polytobacco use among the general population of all adults (ranging from 0.3%−1.6% [28][29][30][31] to 2.5%−3.4% 32,33 and up to 10.6% 34 ), of all men (0.6%−1.6%), 28,[35][36][37] and of all women (0.3%). 36 At the tobacco users' level, the vast majority of studies estimated the prevalence of current polytobacco use among current cigarette smokers (ranging from 2.3%−8.5% 13 , and relatively few studies estimated the prevalence of current polytobacco use among current users of all tobacco products combined (9.9%−12.1% of those aged ≥26 and 21.4%−24.6% of those aged 18−25), 39 among male current snuff users (15.0%−19.2% of daily snuff users and 38.9%−44.7% of nondaily snuff users), 13,37 and among current SLT users (25.0%−42.4%). 30,31,35,36 There is a lack of studies that examine polytobacco use among current cigar users, even though it has been shown that cigars were the most prevalent product concurrently used among current cigarette smokers, 29 and one-half of all polytobacco users consumed both cigarettes and cigars.…”
Section: Original Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…That study focused only on current tobacco users in the Bristol Bay region, and did not differentiate between commercial ST and iqmik . Recent US studies demonstrate that dual- or multi-product use is most prevalent among young adults [16,20,45]. While these studies report up to 30% of young adults are dual product users [19], this percentage is far lower than in AN residents of the Y-K region.…”
Section: Discussionmentioning
confidence: 99%